Cortical Structural Connectivity Alterations and Potential Pathogenesis in Mid-Stage Sporadic Parkinson’s Disease - Deng, Xia; Liu, Zheng; Kang, Qin; Lu, Lin; Zhu, Yu; Xu, Renshi (Frontiers in Aging Neuroscience, 2021)
Many clinical symptoms of sporadic Parkinson's disease (sPD) can’t be completely explained by the lesion of simple typical extrapyramidal circuit between striatum and substantia nigra. Therefore, this study aimed to search the new potential damaged pathogenesis of other brain regions associated with the multiple and complex clinical symptoms of sPD through magnetic resonance imaging (MRI). Sixty-five patients with the mid-stage sPD and 35 healthy controls were recruited in this study. The cortical structural connectivity was assessed by the seed-based analysis using the vertex-based morphology of MRI. Seven different clusters in the brain regions of cortical thickness thinning derived from the regression analysis using brain size as covariates between sPD and control was selected as seeds. Results showed that the significant alteration of cortical structural connectivity mainly occurred in bilateral Frontal Orbital, Opercular, Triangular, Precentral, Rectus, Supplementary-Motor, Temporal Pole, Angular, Heschl, Parietal, SupraMarginal, Postcentral, Precuneus, Occipital, Lingual, Cuneus, Rolandic-Opercular, Cingulum, ParaHippocampal, Calcarine, Olfactory, Insula, Paracentral-Lobule and Fusiform regions at the mid-stage of sPD. These findings suggested that the extensive alteration of cortical structural connectivity is one of possible pathogenesis resulting in the multiple and complex clinical symptoms in sPD.